Recycling Alone or Protesting Together? Values as a Basis for Pro-environmental Social Change Actions - Sloot, Daniel; Kutlaca, Maja; Medugorac, Vanja; Carman, Petra (Frontiers in Psychology, 2018)
Social change can be pursued by participating in a public protest, joining a community gardening initiative, or recycling at home. However, little research has investigated how individual differences in values relate to people’s engagement in different types of social change actions in the context of pro-environmental behaviour. We hypothesised that values would be differentially related to different types of social change actions, based on different goals that each of these actions may have (e.g., changing one’s own behaviour or influencing others). A survey among people engaged in pro-environmental activism during the 2015 United Nations Climate Change Conference supported our predictions. Specifically, we found that individual behaviour and community-based actions were uniquely related to biospheric values (i.e., a key concern for nature and the environment). However, other social change actions (e.g., public protest) were uniquely related to altruistic values (i.e., a key concern for the welfare of all people), and pro-environmental lobbying was positively related to egoistic values (i.e., a key concern for power and achievement). Our findings suggest that different behaviours directed at pro-environmental social change may be based on different values. We discuss the theoretical and practical implications of these findings.